True height description of equatorial F-layer over Parit Raja, Batu Pahat, Malaysia - Zeti Akma, Rhazali; Ahmad Faizal, Mohd Zain (IEEE, 2011)
Digisonde ionograms recorded at Parit Raja, Malaysia (Lat. 1°52′N, Long. 103°48′E, Magnetic dip 14.3°) have been used to study the variations of ionospheric F-layer true height density peak (h max). Hourly and daily patterns of h max as deduced from January 2005 ionograms were analysed and studied to determine the actual F-layer peak height over Malaysia. Initial observations revealed that typical height of equatorial F-layer peak was slightly higher compared to other higher latitude regions. The altitude was found to be around 550±50 km during daytime and 300 km from midnight till pre-sunrise hours.